Macrolide Resistance in the Aerococcus urinae Complex: Implications for Integrative and Conjugative Elements - Jyoti Lamichhane; Brian I. Choi; Natalie Stegman; Melline Fontes Noronha; Alan J. Wolfe (MDPI AG, 2024)
The recognition of the Aerococcus urinae complex (AUC) as an emerging uropathogen has led to growing concerns due to a limited understanding of its disease spectrum and antibiotic resistance profiles. Here, we investigated the prevalence of macrolide resistance within urinary AUC isolates, shedding light on potential genetic mechanisms. Phenotypic testing revealed a high rate of macrolide resistance: 45%, among a total of 189 urinary AUC isolates. Genomic analysis identified integrative and conjugative elements (ICEs) as carriers of the macrolide resistance gene ermA, suggesting horizontal gene transfer as a mechanism of resistance. Furthermore, comparison with publicly available genomes of related pathogens revealed high ICE sequence homogeneity, highlighting the potential for cross-species dissemination of resistance determinants. Understanding mechanisms of resistance is crucial for developing effective surveillance strategies and improving antibiotic use. Furthermore, the findings underscore the importance of considering the broader ecological context of resistance dissemination, emphasizing the need for community-level surveillance to combat the spread of antibiotic resistance within the urinary microbiome.